"Where they (live, work and) spray": Pesticide exposure, childhood asthma and environmental justice among Mexican-American farmworkers. (March 2015) - Schwartz, Norah Anita; von Glascoe, Christine Alysse; Torres, Victor; Ramos, Lorena; Soria-Delgado, Claudia
Abstract: Asthma prevalence is reportedly low for children of Mexican descent compared with other ethnic groups and Latino subgroups. The results of our exploratory ethnographic research among children of farmworkers in California dramatically suggest otherwise. Unstructured and semi-structured open-ended interviews and photovoice methods were combined to explore the lived experiences of members of a marginalized farmworker community. This research gives voice to a population of families living in the highly toxic, yet agriculturally wealthy environment of the San Joaquin Valley. Little work has been reported employing photovoice, a community-based participatory research method, to study childhood exposure to pesticides. A rich narrative about perceptions of pesticide exposure emerged from the ethnographic interviews. Thematic analysis yielded beliefs about the relationship between air quality and childhood asthma. The findings suggest that childhood asthma should be reviewed within the context of local levels of environmental exposure and the principles of environmental justice. Highlights: Asthma rates for Mexican-American children of farmworkers are higher than expected. Children of farmworkers may be exposed to agricultural pesticides at school. Photovoice can be used to elucidate their voices. Childhood asthma should be reviewed within the context of environmental justice.